Pure acceleration is the primary determinant of speed to first-base in Major-League Baseball game situations - Coleman, A. E.; Amonette, W. E. (The Journal of Strength and Conditioning Research, 2012)
The purposes of this research were to (a) quantify interval sprint times between Home-Plate and the Foul-Line and the Foul-Line and First-Base, (b) determine if differences exist in interval velocities and acceleration between left- and right-handed batters or between-position groupings, and (c) to quantify determinants of time to First-Base in Major-League Baseball players during actual games. A total of 1,896 sprint times to the Foul-Line (13.7 m) and First-Base (27.4 m) were recorded in 302 baseball players by a single coach, positioned in the dugout with a hand-held stopwatch. Interval velocities and accelerations were computed between Home-Plate and the Foul-Line and the Foul-Line and First-Base; average velocity and acceleration were also determined over the entire 27.4 m. Velocity and acceleration for left-handed batters were greater than for right-handed batters from Home-Plate to the Foul-Line and from Home-Plate to First-Base; however, there were no differences in velocity or acceleration from the Foul-Line to First-Base. Interval velocity was significantly greater for outfielders and infielders compared with that for catchers from Home-Plate to the Foul-Line and from the Home-Plate to First-Base. Outfielders were faster than catchers from the Foul-Line to First-Base; no other between-group differences were evident. Accelerations from Home-Plate to the Foul-Line and from Home-Plate to First-Base were greater for outfielders compared with infielders and catchers. Infielders accelerated at greater rates than did catchers between these intervals. There were no between-position differences in acceleration from the Foul-Line to First-Base. These data indicate that time to First-Base is most affected by acceleration from Home-Plate to the Foul-Line. Coaches should implement strategies that encourage players to sprint maximally over the first 13.7 m to maximize chances of successfully reaching First-Base.